Perancangan dan Simulasi Antena Mikrostrip Patch Array 2x2 untuk 5G Sub-6 GHz pada Prototipe gNodeB Berbasis SDR - M. Fhadli Haryadi; Lindawati Lindawati; Sopian Soim (CYCLOTRON, 2026)
To address the need for high-gain directional antennas at sub-6 GHz frequencies, this study designed and simulated a 2×2 microstrip patch array antenna based on an FR4 substrate for a 5G gNodeB prototype using a Software Defined Radio (SDR) USRP B210. The antenna utilizes a two-stage corporate feed network based on a Wilkinson Power Divider to distribute power uniformly to the four patch elements. The simulation was conducted over the 2–4 GHz frequency range using CST Studio Suite 2025 software. Simulation results show that the antenna resonates at 3.39 GHz with a return loss (S11) of −11 dB, a VSWR of 1.7, and a maximum gain of 9.808 dBi. The resulting radiation pattern is directional and suitable for sub-6 GHz 5G gNodeB applications. The total efficiency was recorded at −8.846 dB, which is highly influenced by the FR4 substrate losses. Based on these results, the proposed antenna design demonstrates adequate performance for SDR system implementation.